1991
DOI: 10.1159/000138850
|View full text |Cite
|
Sign up to set email alerts
|

Critical Ketoconazole Dosage Range for Ciclosporin Clearance Inhibition in the Dog

Abstract: Ciclosporin (CsA) is metabolized exclusively by the hepatic cytochrome P-450 mixed function oxidase system. Ketoconazole (KC) is a potent inhibitor of this enzyme system. CsA was administered alone and in combination with five different doses of KC (1.25, 2.5, 5.0, 10.0, 20.0 mg/kg/day) under steady-state conditions to 7 adult mongrel dogs. KC produced a highly significant (p = 0.0001), dose-dependent decrease in CsA total body clearance [Cl(T)]. The critical KC dosage range for this to occur was found to be b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 14 publications
(21 reference statements)
1
52
0
1
Order By: Relevance
“…Additionally, inhibition of the CYP 450 enzymes by KTZ has been shown to be dose dependent, which was supported in the present study, with blood and skin CSA concentrations obtained in Treatment 3 being higher than those in Treatment 4. 18 As KTZ inhibition of CYP 450 can affect the metabolism of many other drugs and would be a lifelong therapeutic when paired with CSA for treatment of CAD, it may be important to use the lowest effective KTZ dose to limit the potential degree of interaction with other drugs. 9 Furthermore, it should be noted that in the present study, CSA and KTZ were administered for only 7 days, and the long-term effect of this drug combination on the whole blood and skin CSA concentrations is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, inhibition of the CYP 450 enzymes by KTZ has been shown to be dose dependent, which was supported in the present study, with blood and skin CSA concentrations obtained in Treatment 3 being higher than those in Treatment 4. 18 As KTZ inhibition of CYP 450 can affect the metabolism of many other drugs and would be a lifelong therapeutic when paired with CSA for treatment of CAD, it may be important to use the lowest effective KTZ dose to limit the potential degree of interaction with other drugs. 9 Furthermore, it should be noted that in the present study, CSA and KTZ were administered for only 7 days, and the long-term effect of this drug combination on the whole blood and skin CSA concentrations is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Numerous in vitro and in vivo studies have demonstrated that co-administration of KTZ with CSA results in increased whole blood CSA concentrations in dogs. [13][14][15][16][17][18] The inhibitory effect of KTZ on CSA clearance from blood was determined to be dose dependent, with the critical KTZ dosage range identified as 2.5-10 mg ⁄ kg daily. 18 A study on normal research beagles investigating the dose of KTZ necessary to maintain whole blood CSA trough levels between 400 and 600 mg ⁄ mL showed that KTZ at 13.6 mg ⁄ kg daily enabled a 75% reduction of CSA dose, with estimated monetary savings of 57.8% at that time, and KTZ at 4.7mg ⁄ kg daily reduced CSA dose by 38% and thus reduced cost by 23.8%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of CsA metabolism may be associated with a decrease in the CsA parent:parent + metabolite ratio [12,19], and CsA metabolites are reported to be less immunosuppressive and more toxic than the parent com pound [20,21], In addition, ketoconazole has been re ported to have immunosuppressive activity [12,18,22]. For these reasons, we carried out this prospective ran domized study not only to study CsA dose reduction but also to explore the possible additional biological benefits, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other researchers also reported drug interaction of KTZ with Table 1. cyclosporine in human [19] and dog [5,14] and with midazolam in human [3,7] and dog [10]. The extent of inhibitory effects of KTZ on MDZ1'H and MDZ4H seems to be quite different among animal species.…”
Section: Discussionmentioning
confidence: 99%